Impact of women on board and women CFO towards pay practices in listed companies in Malaysia - Rima Melini, Md Tamin @ Amin (2021)
Director pay and remuneration policy have become contentious issues of late. In Malaysia, Sapura Energy Berhad and Felda Global Ventures Berhad are two recent cases of inexplicably large top management pay not commensurate with company performances, which attracted the attention of investors, regulators, and minority shareholders. Huge pay disparity between top management and employees is also in the spotlight since this pay practice is at odds with the United Nations Sustainable Development Goals (SDG 17) on reducing inequalities. Acknowledging this concern, the latest Corporate Governance Monitor 2020 issued by the Securities Commission continues to highlight the top management pay practices and disclosures. The purpose of this study is to explore the association of women on board and women Chief Financial Officer (CFO) towards the pay disparity, pay disclosure, and Chief Executive Officer (CEO)’s remuneration in listed companies in Malaysia, using the agency, gender, stewardship, stakeholders, and tournament theories. The sample consists of 122 companies listed on Bursa Malaysia. Their compliances with Practices 7.2 and 7.3 of the Malaysian Code on Corporate Governance (MCCG) 2017 are noted. This study found significant relationships between women on board and women CFO towards pay disclosure and CEO remuneration. Supporting the five theories, this study provides the basis for policymakers to emphasize the importance of women on the board and top management as well as contributes to the current debate on the desirability of mandating more women on board and top management.